Rural livelihood diversification is associated with lower vulnerability to climate change in the Andean-Amazon foothills - Beltrán Tolosa, Lucila Marcela; Cruz García, Gisella S.; Ocampo, Jhon; Pradham, Prajal; Quintero, Marcela (2022)
The Andean-Amazon foothills region, one of the richest biodiversity ecoregions on earth, is threatened by climate change combined with unsustainable agricultural and extensive livestock farming. These land-use practices tend to reduce the diversification of rural farming, decreasing households’ livelihood alternatives and rendering them more vulnerable to climate change. We studied the relationship between rural livelihood diversification and household-level vulnerability to climate change in a sample of Andean-Amazon foothills households in Colombia and Peru. Firstly, we determined typologies of households based on their rural livelihood diversification, including farming diversification (agrobiodiversity and farming activities) and agroecological management practices. Secondly, we evaluated each household typology’s vulnerability to climate change by assessing sensitivity and adaptive capacity based on the ‘livelihood assets pentagon’, which encompasses the five human capitals: natural, social, human, physical, and financial. We concluded that households with higher rural livelihood diversification are less vulnerable to climate change. However, it is impossible to draw significant conclusions about the relationship between the factors of diversification of management practices and vulnerability to climate change because most households have few agroecological practices. Results may inform future interventions that aim to decrease Andean-Amazon foothills households’ sensitivity and strengthen their adaptive capacity to climate change.